Pengaruh Kepuasan Kerja terhadap Organizational Citizenship Behavior (OCB) Alumni Diklat Kepemimpinan Tingkat IV di Provinsi Banten - Enong Rostiawati (Lembaga Administrasi Negara, 2020)
Abstract: Organizational Citizenship Behavior (OCB) is a variable that can be influenced by job satisfaction. This study aims to determine the effect of job satisfaction variables on Organizational Citizenship Behavior OCB alumni level IV leadership training in Banten Province. This research uses a quantitative approach through survey methods. Data analysis technique used is simple linear regression. The population in this study were 40 respondents and the sample used was 40 respondents. Determination of the sample using total sampling techniques or samples taken from the entire study population. The results of the analysis and interpretation of research data show that the value of the regulatory coefficient of influence on job satisfaction on Organizational Citizenship Behavior (OCB) alumni of leadership training level IV is 0.740 thus it can be concluded that job satisfaction has a direct positive effect on Organizational Citizenship Behavior alumni training, meaning that improvement of satisfaction in IV level leadership training is 0.740. work has an impact on improving Organizational Citizenship Behavior for training alumni, So Organizational Citizenship Behavior for training alumni can be achieved through job satisfaction.Keywords: Job satisfaction, Organizational Citizenship Behavior, Leadership Training Alumni Level IV